Portuguese Early Literacy Screening Tool- RaLEPE: Pilot Study - Pereira Sapage, Sara; Cruz-Santos, Anabela (Revista de Investigación en Logopedia, 2021)
Early literacy development is an indicator of a child’s overall cognitive-linguistic development and affects their academic, social, emotional and behavioural skills. Research suggests that early detection in preschool years can have an important role in the prevention of academic failure. There is a lack of early literacy screening tools for Portuguese preschool children. This study aims to present preliminary data results of the development and validation of the Preschool Early Literacy Screening Tool (Rastreio de Literacia Emergente Pré-escolar- RaLEPE). A pilot study was carried out with a sample of 128 screenings, answered by the parents/caregivers of the Portuguese children in the target age groups. The analysis of results shown the reliability of the tool, with a very good internal consistency for RaLEPE total scale and the different sections. Therefore, preliminary results of this study indicate internal validity of the RaLEPE and confirm this as screening tool usefulness for early intervention childhood, to provide early diagnosis and contribute to early intervention for children with language and learning disorders.
Keywords: Early Detection; Early Literacy; Portuguese Speaking Children; Preschool Children; Screening Tool